Endocrown restorations: Influence of dental remnant and restorative material on stress distribution - Tribst, João Paulo Mendes [UNESP]; Dal Piva, Amanda Maria de Oliveira [UNESP]; Madruga, Camila Ferreira Leite [UNESP]; Valera, Marcia Carneiro [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Bresciani, Eduardo [UNESP]; de Melo, Renata Marques [UNESP] (Elsevier, 2018)
Objective: The goal of this study was to evaluate the stress distribution in a tooth/restoration system according to the factors “amount of dental remnant” (3 levels) and “restorative material” (2 levels). Methods: Three endodontically treated maxillary molars were modeled with CAD software for conducting non-linear finite element analysis (FEA), each with a determined amount of dental remnant of 1.5, 3, or 4.5 mm. Models were duplicated, and half received restorations in lithium disilicate (IPS e.max CAD), while the other half received leucite ceramic restorations (IPS Empress CAD), both from Ivoclar Vivadent (Schaan, Liechtenstein). The solids were imported to analysis software (ANSYS 17.2, ANSYS Inc., Houston, TX, USA) in STEP format. All contacts involving the resin cement were considered no-separation, whereas between teeth and fixation cylinder, the contact was considered perfectly bonded. The mechanical properties of each structure were reported, and the materials were considered isotropic, linearly elastic, and homogeneous. An axial load (300 N) was applied at the occlusal surface (triploidism area). Results were determined by colorimetric graphs of maximum principal stress (MPS) on tooth remnant, cement line, and restoration. Results: MPS revealed that both factors influenced the stress distribution for all structures; the higher the material's elastic modulus, the higher the stress concentration on the restoration and the lower the stress concentration on the cement line. Moreover, the greater the dental crown remnant, the higher the stress concentration on the restoration. Thus, the remaining dental tissue should always be preserved. Significance: In situations in which few dental remnants are available, the thicker the restoration, the higher the concentration of stresses in its structure, protecting the adhesive interface from potential adhesive failures. Results are more promising when the endocrown is fabricated with lithium disilicate ceramic.
Keywords: Ceramics; Dental restoration failure; Endodontically treated teeth; Finite element analysis; Monoblock restoration